2022
DOI: 10.1093/cercor/bhac177
|View full text |Cite
|
Sign up to set email alerts
|

Temporal irreversibility of neural dynamics as a signature of consciousness

Abstract: Dissipative systems evolve in the preferred temporal direction indicated by the thermodynamic arrow of time. The fundamental nature of this temporal asymmetry led us to hypothesize its presence in the neural activity evoked by conscious perception of the physical world, and thus its covariance with the level of conscious awareness. We implemented a data-driven deep learning framework to decode the temporal inversion of electrocorticography signals acquired from non-human primates. Brain activity time series re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…p(s u , s u−1 ) log p(s u |s u−1 ), (6) which at the steady state corresponds to the Kolmogorov-Sinai entropy or entropy rate, lim t→∞ In stochastic processes in thermodynamic equilibrium, forward and time-reversed trajectories are indistinguishable. Markov processes can break this time-reversal symmetry, capturing the irreversible characteristics of physical and biological processes [38].…”
Section: Maximum Entropy Markov Chains Entropy Production and Generat...mentioning
confidence: 99%
See 3 more Smart Citations
“…p(s u , s u−1 ) log p(s u |s u−1 ), (6) which at the steady state corresponds to the Kolmogorov-Sinai entropy or entropy rate, lim t→∞ In stochastic processes in thermodynamic equilibrium, forward and time-reversed trajectories are indistinguishable. Markov processes can break this time-reversal symmetry, capturing the irreversible characteristics of physical and biological processes [38].…”
Section: Maximum Entropy Markov Chains Entropy Production and Generat...mentioning
confidence: 99%
“…Recently, nonequilibrium properties of biological and intelligent systems have received the attention of neuroscience and biological science communities. For example, increased entropy production in macroscopic neural activity was suggested as a signature of physically and cognitively demanding tasks [4], conscious activity [5,6] or neuropsychiatric diseases like schizophrenia, bipolar disorders, and ADHD [7]. While it is not easy to contrast their findings based on the coarse-grained analysis of ECoG or fMRI data with the present results, our precise characterization of the entropy production of the pro-totypical system sheds light on what kind of behaviours we might expect from these complicated systems.…”
Section: Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent neuroimaging endeavours further substantiate this potential: after training a deep learning network to distinguish between temporal segments of forward and backward fMRI time series, Deco et al31 not only observed a variable AoT strength (inferred from classification accuracy on unseen data) across cognitive states, but also between healthy subjects and patients suffering from bipolar disorder, attention deficit hyperactivity disorder or schizophrenia. In another study leveraging the same framework on electrocorticography data, de la Fuente et al44 also revealed that deep sleep and ketamine-induced anesthesia lowered the differences between forward time series and their inverted counterparts, i.e., decreased AoT strength.…”
mentioning
confidence: 94%